Do more get more: Monopoly appropriation of labor income in manufacturing companies - Wei, Cui; An-Wei, Wan; Kumari, Sonia (Frontiers in Environmental Science, 2022)
In recent years, the overtime culture has generally emerged in Chinese enterprises (CEs), the length of workers' working hours has been lengthened, and their intensity has increased. Still, the labor income share has declined, which deserves in-depth analysis. This paper introduces a relative labor intensity indicator to estimate the trend of the labor income share based on the general factor-enhanced CES production function in China. The econometric model is then introduced to analyze in-depth the influencing factors leading to this trend using relevant data from 2001 to 2020. If the elasticity of substitution is less than 1 and capital and labor are complementary, then the labor income share tends to decrease. This is because the relative labor intensity tends to increase while the growth rate of the capital-labor ratio tends to decrease. The empirical results also show that the decrease in labor income share and labor compensation is related to monopoly and the amount of capital input. If the amount of capital input is higher and the degree of monopoly is higher, then the labor income is lower, and the share of labor income is lower. Monopolies and capital intercept most of the value created because of the increased labor intensity, and laborers receive only a small profit.